Desain Modul Ajar dengan Pendekatan PBL Pada Pembelajaran Matematika di Sekolah Dasar - Ermawasari, Ermawasari; Ahmad, Syafri; Salmaini, Salmaini (Universitas Pahlawan Tuanku Tambusai, 2024)
This teaching module is designed to implement the Problem-Based Learning (PBL) approach in mathematics learning in elementary schools (SD). PBL is a learning method that focuses on solving real problems as a learning center, allowing students to learn actively and contextually. Through this approach, students not only gain an understanding of mathematical theories, but are also trained to think critically and creatively in solving mathematical problems related to daily life. This module includes a variety of activities involving problem solving, group discussions, exploration of mathematical concepts, and the application of mathematical knowledge in real-life situations. The topics discussed are adapted to the mathematics curriculum in elementary school, such as measurement, geometry, numbers, and basic operations, which are presented in the form of contextual problems that are relevant to the student's surrounding environment. The application of the PBL approach in mathematics learning is expected to increase learning motivation, problem-solving skills, and a deeper and more applicable understanding of mathematical concepts for students. Thus, this teaching module aims to create a more enjoyable and meaningful learning experience for students, as well as support the achievement of higher mathematical competencies at the elementary level.